A LOOK AT THE WORK OF JONATHAN SWIFT (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2024)
This article provides a scientific and theoretical analysis of the artistic and poetic features of the works of Jonathan Swift